2016
DOI: 10.1104/pp.15.01872
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Activity and 3′phosphadenosine 5′phosphate Signaling Regulate Programmed Cell Death in Arabidopsis

Abstract: Programmed cell death (PCD) is a crucial process both for plant development and responses to biotic and abiotic stress. There is accumulating evidence that chloroplasts may play a central role during plant PCD as for mitochondria in animal cells, but it is still unclear whether they participate in PCD onset, execution, or both. To tackle this question, we have analyzed the contribution of chloroplast function to the cell death phenotype of the myoinositol phosphate synthase1 (mips1) mutant that forms spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
(83 reference statements)
1
24
0
Order By: Relevance
“…As many of these commonly regulated genes are ANAC017 dependent, it was recently suggested that the PAP and ANAC017 pathways are mechanistically linked (Van Aken and Pogson, 2017). At least part of this common pathway appears capable of suppressing cell death and lesion formation, potentially by suppressing, e.g., extrusion of toxic compounds such as chlorophyll degradation products (Bruggeman et al, 2016;Van Aken and Pogson, 2017).…”
Section: Phosphoadenosine Phosphatementioning
confidence: 99%
“…As many of these commonly regulated genes are ANAC017 dependent, it was recently suggested that the PAP and ANAC017 pathways are mechanistically linked (Van Aken and Pogson, 2017). At least part of this common pathway appears capable of suppressing cell death and lesion formation, potentially by suppressing, e.g., extrusion of toxic compounds such as chlorophyll degradation products (Bruggeman et al, 2016;Van Aken and Pogson, 2017).…”
Section: Phosphoadenosine Phosphatementioning
confidence: 99%
“…Besides their central role in carbon and energy metabolism, both mitochondria and chloroplasts have also been implicated as key players in various plant cell death signaling pathways (Mühlenbock et al , Zurbriggen et al , van Doorn et al , Pattanayak et al , Bruggeman et al , Huang et al , Dickman et al , Dogra et al ). This influence likely relates to the critical role of these organelles in energy metabolism, as well as their capacity to engage various and likely interconnected signaling pathways, some of which promote cell death (Baena‐González and Sheen , Green et al , Van Aken and Pogson ).…”
Section: Introductionmentioning
confidence: 99%
“…ex1 ex2 double mutants cannot rescue the ROS-dependent necrotic phenotype of fc2 mutants (discussed at length below) nor the lesion mimic phenotype of mips1 ( myoinositol phosphate synthase1 ) mutants. Like several other lesion mimic mutants, mips1 lesion formation is light- and chlorophyll-dependent [13], and can be suppressed in the dark or in mutant backgrounds defective in chlorophyll biosynthesis (including mutants defective in Mg chelatase activity, gun4 and gun5 , and a mutant defective in divinyl protochlorophyllide 8-vinyl reductase activity, pcb2 ) [14]. A reverse genetic screen for suppressors of the mips1 lesion formation identified sal1/fiery1 as a strong suppressor of mips1 PCD [14].…”
Section: Chloroplasts Choosing Between Life and Death: Paps And Execumentioning
confidence: 99%
“…Like several other lesion mimic mutants, mips1 lesion formation is light- and chlorophyll-dependent [13], and can be suppressed in the dark or in mutant backgrounds defective in chlorophyll biosynthesis (including mutants defective in Mg chelatase activity, gun4 and gun5 , and a mutant defective in divinyl protochlorophyllide 8-vinyl reductase activity, pcb2 ) [14]. A reverse genetic screen for suppressors of the mips1 lesion formation identified sal1/fiery1 as a strong suppressor of mips1 PCD [14]. SAL1 localizes to chloroplasts and mitochondria, where it dephosphorylates PAP (3′ phosphoadenosine 5′ phosphate) into AMP, but sal1 mutants hyperaccumulate PAP without dramatic effects on the levels of PAP precursors [15] (Figure 1C).…”
Section: Chloroplasts Choosing Between Life and Death: Paps And Execumentioning
confidence: 99%
See 1 more Smart Citation